SAHAM SYARIAH: AKAD-AKAD SAHAM SYARIAH DAN PRAKTIKNYA DI NEGARA INDONESIA & QATAR - Silviany, Ratih; Awaliyah, Annisa Fitri; Anantha, Agung; Sabila, Wan Shalah; Batubara, Maryam (LPPM STAI Muhammadiyah Probolinggo, 2025)
Sharia-compliant stocks represent a rapidly growing investment instrument in line with increasing awareness of Islamic economic principles. Unlike conventional stocks, Sharia stocks are based on specific Islamic contracts (akad) such as musyarakah and mudharabah, ensuring transactions comply with Sharia law. This paper aims to explore the types of Sharia contracts applied in equity investment and compare their practical implementation in two distinct Islamic financial environments: Indonesia and Qatar. Using a normative-comparative approach and literature review methodology, this study examines the regulatory frameworks, fatwas, and institutional structures governing Sharia capital markets in both countries. The findings reveal that while both nations uphold the foundational principles of Islamic finance prohibiting riba (interest), gharar (excessive uncertainty), and maysir (speculation) they differ significantly in the operationalization of Sharia compliance. Indonesia relies heavily on the Fatwa of the National Sharia Council (DSN-MUI) and supervision by the Financial Services Authority (OJK), whereas Qatar applies standards from AAOIFI and localized Sharia boards. This study contributes to the growing discourse on Sharia capital market harmonization and provides insights for policymakers to enhance Sharia equity frameworks that align with maqasid al-shariah.